Mediating Role of the Six Sigma Implementation Strategy and Investment in Human Resources in Economic Success and Sustainability - García-Alcaraz, Jorge Luis (2018)
Six Sigma is a methodology widely used in manufacturing production to guarantee quality and several factors facilitate its success. This paper presents a structural equations model to identify the relationships between managerial commitment, Six Sigma implementation strategy, investments in human resources and the economic beneﬁts obtained; and ﬁve hypotheses are proposed. These variables are also related to sustainability, especially human resources, a paradigm very combinable with Six Sigma. The model is evaluated using partial least squares and information obtained from 301 Mexican manufacturing companies from different industrial sectors. The results indicate that managerial commitment is the basis for Six Sigma success, but requires an adequate implementation strategy focused on customers and their needs, which must integrate an investment plan in human resources that is focused on training and teamwork. In addition, managers must have a reward program that encourages motivation and recognizes the achievements of the human resources involved.